1.2.3. Synthesis and Structural Characterization of [Co0.5(bimb)1.5] n·nClO4 (bimb =1,4-bis(imidazol-1-yl)-butane) (Communications in Inorganic Synthesis, 2014)
Abstract: A new cobalt(II) coordination polymer, namely [Co0.5 (bimb)1.5]n·nClO4 (bimb =1,4-bis(imidazol-1-yl)-butane)Â  (1), has been prepared and fully characterized by single-crystal X-ray diffraction, elemental analyses, IR spectroscopy and X-ray powder diffraction pattern analysis (PXRD). Of the compound, the Co(II) center is octahedral coordinated with bimb serving as a bridging ligand by employing six N-donor to coordinate with the Co(II) center. It exbihits three-dimensional network structure via bimb ligands. Supporting information: CIF file.